The relationship between intimate partner violence and postpartum depression in Osogbo, Nigeria - Abiodun, Adejoke D.; Mapayi, Boladale; Abiodun, Afolabi B.; Mosanya, Julianah T.; Adeomi, Adeleye A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Postpartum depression is the most prevalent postpartum mental health problem. Risk factors for postpartum depression include psychosocial stressors. One of these psychosocial stressors could be intimate partner violence. Co-occurrence of intimate partner violence and postpartum depression is considered deadly co morbidity because it can increase the risk of homicide and suicide. The aim of this study was to determine the relationship between intimate partner violence and depression among postnatal women attending postnatal and infant welfare clinics of LAUTECH Teaching Hospital, Osogbo. Methods: A descriptive cross-sectional study was conducted among 220 postpartum women who attended postnatal and infant welfare clinics of LAUTECH Teaching Hospital in Osogbo using Composite Abuse Scale (CAS), Edinburgh Postnatal Depression Scale (EPDS) and Socio-demographic questionnaire. Respondents that were found to be EPDS positive as well as 10% of EPDS negative respondents were further assessed with Mini International Neuropsychiatric Interview (MINI) (depression subscale) to diagnose depression. Results: Respondents that experienced intimate partner violence were five times as likely to have postpartum depression compared to those that did not experience IPV. Logistic regression showed that intimate partner violence independently predicted postpartum depression in respondents (OR 4.799, CI 1.844-12.493). Conclusions: Postpartum depression was significantly higher among women that experienced intimate partner violence. This observation has implications for mental health of women, therefore, any woman with suspected postpartum depression should be asked about IPV as this could be a pointer to IPV.